An extremely rare neoplasm, histiocytic sarcoma: A report of two cases with an aggressive clinical course - Erkan Kayikcioglu; Asim Armagan Aydin; Arif Hakan Onder; Alper Sayiner; Dinc Suren; Banu Ozturk (Journal of Oncological Sciences, 2017)
Histiocytic sarcoma (HS) is an extremely rare malignant neoplasm accounting for less than 1% of all hemato-lymphoid neoplasms. Sixty percent of all cases are metastatic at presentation and the prognosis is poor. Two cases of HS with an aggressive clinical course are presented. The first case was a 58-year-old man admitted to our hospital with back pain and paresthesia of the lower extremities. Magnetic resonance imaging (MRI) of the thoracic spine revealed a mass measuring 48 × 15 mm between the T2‒T5 paravertebral area, entering the spinal channel via the neural foramen and compressing the spinal cord. The mass was completely resected and pathological and immunohistochemical staining confirmed the diagnosis of HS. After three cycles of cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) and two cycles of carboplatin/paclitaxel, the patient died due to disease progression after 9 months. The second case is a 48-year-old man who presented with fever and weight loss, and complained of back pain for 2 months. Thoracic vertebral MRI revealed a lesion destructing the T6, T7 and T9 vertebral corpus and a mass measuring 2.5 × 2 cm near the T6‒T7 transverse process. Total-body fluorodeoxyglucose positron emission tomography (FDG-PET) imaging revealed bilateral inguinal hypermetabolic lymph nodes measuring 10 × 14 mm and osteolytic destructive bone lesions on the vertebral colon and pelvic bones. Pathological and immunohistochemical staining of bone marrow aspirate confirmed the diagnosis of HS. After three cycles of ifosfamide, carboplatin, etoposide (ICE) chemotherapy, the patient died due to disease progression after 3 months. Conclusions: HS is an extremely rare malignant neoplasm of the monocytic/macrophage lineage, with no standardized chemotherapy regimen for multisystemic disease. Metastatic patients have a more aggressive clinical course than those with unifocal disease.